64 MS-CTU: Review of techniques and spectrum of the ureteric diseases. Issue 3 (1st September 2018) - Agha, Mahmoud; Eid, Ahmed Fathi
Abstract: Objective: The study aims to clarify the sensitivity of the CTU, and if is it coast effective and time effective to be used as first and the one-stop shop imaging modality for the diagnosis of the different ureteric diseases. Patients and methods: 400 patients with different urinary tract complaints (hematuria and/or renal colic) did triphasic CTU examinations, for diagnosis of suspected obstructive or traumatic ureteric uropathy from January 2014 to October 2016. These patients were filtered from a larger number of patients – who were presented with urinary tract complaints by plain KUB X ray and US, which showed no explaining kidneys or urinary bladder pathology. Results: Ureteric duplication was detected in 5 (1.25%) patients, ectopic ureter in one patient (0.25%), UPJ stricture in 4 patients (1%), PUJ vascular impression in 2 patients (0.5%), ureteric calculus in 103 patients (25.75%), pyogenic ureteritis in 8 patients (2%), ureteritis cystica in one patient (0.25%) TCC in 3 patients (0.75%), PRPF in one patient (0.025%) and Trauma in one patient (0.025%). Conclusion: CTU is very sensitive tool of imaging and could be confidently considered the one-stop shop imaging tool for accurate diagnosis of the different ureteric lesions.